2022
DOI: 10.1039/d1tc06054f
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of asymmetric indolonaphthyridines with enhanced excited state charge-transfer character

Abstract: Indolonaphthyridines (IND) are valuable chromophores with wide-ranging optoelectronic applications. Here, we present a new class of asymmetric IND derivatives, synthesised using novel high yielding methodology. We compare the absorption properties...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 34 publications
0
7
1
Order By: Relevance
“…Therefore, the increased ability for OHAC to undergo singlet fission is a result of heightened electronic coupling, as opposed to improved energy-level alignment. Electronic coupling to TT states can often be charge-transfer mediated in singlet fission, and a previous study by our group showed that INDT derivatives have charge-transfer contribution to the photoexcited S 1 state . Therefore, while we did not observe direct evidence of charge transfer states in the TA data, it is possible the singlet fission mechanism may be charge-transfer mediated in OHAC.…”
Section: Resultscontrasting
confidence: 74%
“…Therefore, the increased ability for OHAC to undergo singlet fission is a result of heightened electronic coupling, as opposed to improved energy-level alignment. Electronic coupling to TT states can often be charge-transfer mediated in singlet fission, and a previous study by our group showed that INDT derivatives have charge-transfer contribution to the photoexcited S 1 state . Therefore, while we did not observe direct evidence of charge transfer states in the TA data, it is possible the singlet fission mechanism may be charge-transfer mediated in OHAC.…”
Section: Resultscontrasting
confidence: 74%
“…However, a recent study by our group showed IND desymmetrization can blue shift IND excited state energies. Therefore, synthesis of asymmetric IND dimers may improve the triplet energy for solar cell application [44] …”
Section: Synthesis and Dimer Designmentioning
confidence: 99%
“…Therefore, synthesis of asymmetric IND dimers may improve the triplet energy for solar cell application. [44]…”
Section: Synthesis and Dimer Designmentioning
confidence: 99%
“…Our efforts were crowned with the first total syntheses of melovinone (5) and waltherione-F (6). 9 During these studies, we also noticed that compounds like 7 are synthetic intermediates to new materials of importance in optoelectronics 10 and that 8 is a potent and selective inhibitor of the enzyme monoamino-oxidase B (MAO B, IC 50 = 0.66 nM). 11 We also realized that certain 4-substituted isatins like 9 induce dopaminergic or D2-agonist activity useful for treating hypertension 12a and others such as 10 proved to be relevant inhibitors of enzyme CDK2.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Our efforts were crowned with the first total syntheses of melovinone ( 5 ) and waltherione-F ( 6 ) . During these studies, we also noticed that compounds like 7 are synthetic intermediates to new materials of importance in optoelectronics and that 8 is a potent and selective inhibitor of the enzyme monoamino-oxidase B (MAO B, IC 50 = 0.66 nM) …”
Section: Introductionmentioning
confidence: 99%